Ame, assuma e consuma: canções, censura e crônicas sociais no Brasil de Odair José (1972-1979) - Cavalcanti, Ivan Luis Lima (2015)
This study approaches the work of the singer Odair José as a social chronicle of the Brazilian society from 1972 to 1979. We start off with a short biographical report of the artist and observe his migration to Rio de Janeiro and the importance of this fact to the composition of his songs and his insertion in the so-called brega music. From the lyrics of this artist we establish an analysis of the country in a moment of moral and political repression and of radicalization even in the artistic field. Aspects of the everyday life, of the loving relations, of the social polemics, of the moral transgressions and of the censorship were essential characteristics of his work. By analysing radio files, newspapers, disc sales records and censored lyrics that have recently been liberated by Arquivo Nacional, this research intends to examine historical and political processes through the lyrics of a singer that truly represented a complex Brazil in his songs; a singer that reached a great popular success both in sales and in the radios; was censored by the military regime; and brought to life debates that hadn’t been present in songs yet.